1989
DOI: 10.1093/jn/119.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoenolpyruvate Carboxykinase of Rat Small Intestine: Distribution and Regulation of Activity and mRNA Levels

Abstract: Phosphoenolpyruvate carboxykinase (PEPCK) activity is present along the length of rat small intestine and in enterocytes throughout the villus-crypt axis. There is no detectable activity in submucosal layers. Messenger RNA encoding PEPCK is detectable in rat intestinal mucosa and the relative abundance increases markedly (3- to 8-fold) during starvation or streptozotocin-diabetes. However, these changes are not matched by changes in enzyme activity which are only slightly increased (1.5-fold). The intestine of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…2) [16]. This observation is similar to the diabetes-induced increase in the number of transcripts for intestinal phosphoenolpyruvate carboxykinase which was not matched by any comparable increase at the protein level [52].…”
Section: Resultssupporting
confidence: 54%
“…2) [16]. This observation is similar to the diabetes-induced increase in the number of transcripts for intestinal phosphoenolpyruvate carboxykinase which was not matched by any comparable increase at the protein level [52].…”
Section: Resultssupporting
confidence: 54%
“…Expression of β-actin and GAPDH mRNA, which are frequently used as internal standards for mRNA levels, were elevated 2-to 3-fold, while that of albumin mRNA decreased drastically after the two 5 day periods of fasting. Previous studies have demonstrated a decrease in the levels of some mRNA species in rat liver after various periods of fasting (60,61), but the levels of other mRNA species increase in liver (62) and small intestine (63) when rats are fasted for up to 7 days. Others have reported significant decreases in functional albumin mRNA upon shortterm fasting (64).…”
Section: Discussionmentioning
confidence: 92%
“…Calculations from succinate-C02 ratio ( 14C02 from [ 1 ,4-14C]succinate: l4Co2 from [2,3-14C]succinate) or from acetate-C02 ratio (14C02 from [l-14C]acetate: I4CO2 from [2-14C]acetate) in the presence of glutamine predicts that glutamine molecules entering the tricarboxylic acid cycle have a low probability of remaining in the cycle for a complete turn (Mallet et al 1986b;Fleming & Kight, 1994 . Because the addition of 3-mercaptopicolinate, an inhibitor of PEPCK, has no effect on glutamine oxidation, PEPCK plus pyruvate kinase may play only a minor role in the second decarboxylation of glutamine-C and the generation of pyruvate and alanine (Hanson & Parsons, 1977;Watford et al 1979;Watford & Tatro, 1989;Watford, 1994). Similarly, the step catalysed by oxaloacetate decarboxylase probably does not make a significant contribution to the decarboxylation of glutamine.…”
Section: Sclection De Substrats Cnergktiques Dans Les Cellules Intestmentioning
confidence: 99%